2005
DOI: 10.1084/jem.20042307
|View full text |Cite
|
Sign up to set email alerts
|

The macrophage F4/80 receptor is required for the induction of antigen-specific efferent regulatory T cells in peripheral tolerance

Abstract: We show that the mouse macrophage-restricted F4/80 protein is not required for the development and distribution of tissue macrophages but is involved in the generation of antigen-specific efferent regulatory T (T reg) cells that suppress antigen-specific immunity. In the in vivo anterior chamber (a.c.)–associated immune deviation (ACAID) model of peripheral tolerance, a.c. inoculation of antigen into F4/80−/− mice was unable to induce efferent T reg cells and suppress delayed-type hypersensitivity (DTH) respon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

13
240
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 326 publications
(253 citation statements)
references
References 59 publications
13
240
0
Order By: Relevance
“…F4/80 KO animals show normal development of tissue Mf populations [7] and normal responses to infectious challenge with Listeria [18]. On the basis of previous studies with the ACAID (anterior chamber-associated immune deviation) model, Stein-Streilein and colleagues provided evidence that the F4/80 molecule is required for peripheral tolerance to ovalbumin administered in the anterior chamber of the eye, as well as for low-dose oral tolerance [7]. F4/80…”
Section: Functionmentioning
confidence: 99%
See 1 more Smart Citation
“…F4/80 KO animals show normal development of tissue Mf populations [7] and normal responses to infectious challenge with Listeria [18]. On the basis of previous studies with the ACAID (anterior chamber-associated immune deviation) model, Stein-Streilein and colleagues provided evidence that the F4/80 molecule is required for peripheral tolerance to ovalbumin administered in the anterior chamber of the eye, as well as for low-dose oral tolerance [7]. F4/80…”
Section: Functionmentioning
confidence: 99%
“…Subsequent cloning by Andrew McKnight et al [5] revealed that F4/80 is a seven-span transmembrane molecule with a large extracellular domain consisting of multiple EGF modules, and is related to another myeloid antigen, CD97, described by Jörg Hamann et al [6]. No natural ligand has been defined for F4/80 and its function remained mysterious till studies on F4/80 knockout mice, by Hsi-Hsien Lin, Joan Stein-Streilein and colleagues, who revealed a role in peripheral tolerance [7].…”
Section: Introductionmentioning
confidence: 99%
“…The functional contexts in which different aGPCR paralogs serve is very diverse, ranging from immunity, synapse function, planar cell polarity, tumor progression, and fertility (Usui et al, 1999;Steinert et al, 2002;Davies et al, 2004;Lin et al, 2005). Unraveling aGPCR function has not been possible for most class members due to the lack of knowledge about physiological stimuli and intracellular coupling to signaling cascades, and suitable in vivo models.…”
Section: Introductionmentioning
confidence: 99%
“…Although a cellular ligand might be anticipated, molecules interacting with F4/80 have not yet been identified. F4/80-deficient mice are healthy and do not show abnormalities in macrophage development and function [14,15]. However, Lin et al [15] have recently provided the first clue to the function of F4/80 by demonstrating a role in the induction of peripheral tolerance.…”
Section: Introductionmentioning
confidence: 99%